DETERMINANTS OF ENTREPRENEURIAL INTENTIONS OF WOMEN ENTREPRENEURS IN INDONESIA - Purwanto, Purwanto; Wahab, Wahab; Latip, Abdul; Elizabeth, Misbah Zulfa (Jurnal Manajemen dan Kewirausahaan, 2025)
This paper seeks to demonstrate that the integrated theory of planned behavior (TPB) and entrepreneurial orientation theory significantly influence the entrepreneurial intentions of women entrepreneurs in upper-middle-income countries, particularly in Indonesia. The research provides empirical evidence highlighting the combined effect of TPB and entrepreneurial orientation on women's motivation to engage in entrepreneurial activities. The findings emphasize the significance of subjective standards, offering essential recommendations for policymakers and educators seeking to foster female entrepreneurship in similar economic contexts. The study utilized a quantitative approach through a cross-sectional survey of 329 women entrepreneurs selected via convenience sampling. Data collection employed a standardized questionnaire, modified from previous studies, with responses assessed using a five-point Likert scale. Analytical methods included partial least squares structural equation modelling (PLS-SEM) to assess both measurement and structural models. The findings indicate that the components of TPB and entrepreneurial orientation considerably impact entrepreneurial intentions, with subjective norms having the most substantial effect. The study provides practical recommendations for policymakers and organizations that help entrepreneurs, highlighting the importance of enhancing social support for women entrepreneurs through initiatives such as mentorship programs and entrepreneurship training. These proposals seek to promote entrepreneurial advancement among women in Indonesia and other countries with comparable economic characteristics.